Evaluation of the pediatric-centered integrated care AOK Junior: protocol for a mixed-method study - Sebastian Liersch; Kathrin Krüger; Carina Oedingen; Andrea Spreenberg; Torben Bergemann; Christian Krauth (BMC, 2020)
Abstract Background The "AOK-Junior" care program of the AOK Nordost (a German statutory health insurance) completes the primary care for children and adolescents (C&A) in the federal states of Berlin, Brandenburg and Mecklenburg-Vorpommern in Germany. The focus of this program is on prevention and early detection of illness on C&A. Furthermore, the aim is to maintain the health of C&A and to prevent, detect and treat illness on time. Elements of the program are not only the integrated care of C&A, but also, for example, weight reduction and additional medical checkups U10, U11 and J2. The evaluation of the complex intervention should provide information about the effectiveness of early disease detection and costs-effectiveness as well as of other parameters like satisfaction. Methods The evaluation is performed on the levels of structural-, process- and results-quality. The cost effectiveness is also assessed by means of a health economic evaluation. In addition to the collection of qualitative and quantitative primary data from participating and non-participating C&A and paediatricians, routine data from a statutory health insurance are used in the evaluation. Furthermore, a cross-sectional design is used to evaluate the structure and process quality. The effectiveness is evaluated in longitudinal section design on the basis of the secondary data. The quantitative surveys include net n = 1096 C&A and n = 340 pediatricians. For the focus groups, a sample of 72 to 96 parents as well as pediatricians will be sought by using the method of theoretical sampling. Discussion Around 560 pediatricians and 63,000 C&A currently participate in the AOK Nordost care program. The project provides information to what extent secondary preventive measures can lead to the early detection of diseases and on the associated cost-effectiveness. Furthermore, potentials and barriers of the program implementation are identified. The results of the evaluation study are expected not only to contribute to the further development of the care program, but also to derive recommendations for action. Trial registration German Clinical Trials Register (DRKS), DRKS-ID: DRKS00015280 . Prospectively registered on 18 March 2019.